MODEL PEMBELAJARAN MATEMATIKA KNISLEY UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEPTUAL MATEMATIS SISWA SMP - Wieka Septiyana; Heni Pujiastuti (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
Mathematical conceptual understanding is a provision in solving problems and finding other concepts. Therefore, this research should be conducted to determine the mathematical learning model that can enhance these capabilities. The main objective is to investigate and describe the achievement as well as an increase in the mathematical ability of conceptual understanding both got teaching Knisley mathematics learning model and direct learning model. The method used mixed method (mixed methods) with the incorporation of quantitative and qualitative models. The study design used concurrent embedded design. The population in this research is class VIII SMP with sample class VIII A and B. Class selected as sample using purposive sampling technique. Quantitative data analysis in this study using the samples Independent-T test and Mann-Whitney. Results of descriptive statistical analysis showed the experimental class =0.83, =14.92 and =0.58. And a control class shows = 0.89, = =10.27 and =0.39. Based on the test results of the samples Independent-T test to determine achievement and test scores N-gain KPKM each student obtained the data with sig (one-tailed) and =0.05 is 0.000. Because of sig < 0.05 then rejected that hypothesis is accepted. Thus, the research concludes that the attainment and improved conceptual understanding of mathematical ability of students who get teaching mathematics learning model Knisley better than who received direct instruction.